2014
DOI: 10.1111/ijfs.12385
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vacuum cooking treatment on physicochemical and structural characteristics of purple‐flesh potato

Abstract: 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 The cooking treatments could combine pairing conditions of time and temperature, therefore an adequate 50 experimental design is imperative to provide proper conclusion. Response Surface Methodology (RSM) is a useful 51 experimental design to explore relationships between several variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 46 publications
1
8
0
1
Order By: Relevance
“…This effect leads to loss of anthocyanin color, since the aglycone forms are more stable than their glycosidic forms. In this sense, both anthocyanin losses and color reduction have been reported by Iborra‐Bernad et al () and Hoon‐Moon et al . () in potato samples subjected to temperatures from 60 to 92C.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…This effect leads to loss of anthocyanin color, since the aglycone forms are more stable than their glycosidic forms. In this sense, both anthocyanin losses and color reduction have been reported by Iborra‐Bernad et al () and Hoon‐Moon et al . () in potato samples subjected to temperatures from 60 to 92C.…”
Section: Discussionmentioning
confidence: 52%
“…This effect leads to loss of anthocyanin color, since the aglycone forms are more stable than their glycosidic forms. In this sense, both anthocyanin losses and color reduction have been reported by Iborra-Bernad et al (2015) and Hoon-Moon et al (2015) in potato samples subjected to temperatures from 60 to 92C. It has also been reported that light accelerates the degradation of anthocyanins (Markakis 1982), particularly when fluorescent light is combined with slightly elevated storage temperatures (Palamidis and Markakis 1978).…”
Section: Discussionmentioning
confidence: 78%
“…The knowledge of how each type of cooking treatment can affect each vegetable could be interesting to increase the quality of the ready‐to‐eat products. Therefore, studies applying different cooking treatments on the same product (Chiavaro and others ; Iborra‐Bernad and others ; Lachman and others ) are relevant to select the right culinary factors and increase the nutritional and sensorial quality offered to consumers.…”
Section: Introductionmentioning
confidence: 99%
“…And the processed tissues could become more deformable producing a softer and rubbery texture (Loredo et al 2014). Similarly, after vacuum-boiled treatments potato tissues become lower hardness and cohesiveness because of the cell turgidity loss (Iborra-Bernad et al 2014). Besides, cell wall components (especially cellulose) possess the function of maintaining the rigidity and resistance of tissues.…”
Section: Tpa Parametermentioning
confidence: 99%